Ethically dubious Human Resources Management practices: An exploratory study of HR professionals’ perceptions - Simões, E.; Duarte, A.P.; Neves, J.; Silva, V. H. (VII Conference Research and Intervention in Human Resources, 2017)
Currently, most organizations assume corporate social responsibility as an important purpose, and ethical scrutiny in all areas of organizational life is seen as a natural consequence of this option. However, practices and the currently prevailing discourse of Human Resources Management (HRM) seem to ignore those concerns (Pinnington, Macklin, & Campbell, 2007). Emphasis on strategic alignment has led HRM’s agents to focus primarily on organizational rationality and control, highlighting the importance of HRM to corporate profitability, preferring thereby to distance themselves from a certain humanistic matrix of HRM’s historical origins (Dale, 2012; Jack, Greenwood, & Schapper, 2012). The main goal of the present study with HR professionals (N=149; 66% females; M age= 43 years old; M tenure=11 years; 43% with a management position) was to examine the acceptability of ethically dubious HRM practices, taking into account the existence and the practical salience of ethical infrastructures (e.g., codes of conduct, compliance and ethics programs) (Treviño, den Nieuwenboer, & Kish-Gephart, 2014) and the perception of corporate social responsibility practices in their organizations. Members of a Portuguese HRM association were invited to participate in the study by email. The email explained the aims of the study and made available a link to an electronic survey containing measures of the aforementioned variables of interest. Findings revealed that the degree of practical salience given to ethical infrastructures predicts the acceptability level of ethically dubious practices, with participants from high salience organizations judging the practices of personal disregard (e.g. “Recommend a problematic worker for other area of the organization”) as more acceptable than those of discrimination (e.g. “Do not select candidates of a certain ethnic group”) and power favoring (e.g. "Facilitate the process of selecting a relative of a senior official of the organization). HRM discrimination practices are also less acceptable to the participants from organizations that are perceived as more responsible in any CSR dimension (economic, community and internal). Power favoring practices in HRM tend to be less acceptable to those working in organizations considered more socially responsible economically. Practical implications of the overall results for the enhancement of ethicality of HRM practices are discussed.